Active power line conditioners : design, simulation and implementation for improving power quality - Salmeron Revuelta, Patricio; Prieto Thomas, Jaime; Perez Litran, Salvador (Elsevier, 2016)
Active Power Line Conditioners: Design, Simulation and Implementation for Improving Power Quality presents a rigorous theoretical and practical approach to active power line conditioners, one of the subjects of most interest in the field of power quality. Its broad approach offers a journey that will allow power engineering professionals, researchers, and graduate students to learn more about the latest landmarks on the different APLC configurations for load active compensation. By introducing the issues and equipment needs that arise when correcting the lack of power quality in power grids.